Higher rates of cefiderocol resistance among NDM producing Klebsiella bloodstream isolates applying EUCAST over CLSI breakpoints - (:unkn) unknown (My University, 2023)
Background: Cefiderocol is generally active against carbapenem-resistant Klebsiella spp. (CRK) with higher MICs against metallo-beta-lactamase producers. There is a variation in cefiderocol interpretive criteria determined by EUCAST and CLSI. Our objective was to test CRK isolates against cefiderocol and compare cefiderocol susceptibilities using EUCAST and CLSI interpretive criteria. Methods: A unique collection (n = 254) of mainly OXA-48-like- or NDM-producing CRK bloodstream isolates were tested against cefiderocol with disc diffusion (Mast Diagnostics, UK). Beta-lactam resistance genes and multilocus sequence types were identified using bioinformatics analyses on complete bacterial genomes. Results: Median cefiderocol inhibition zone diameter was 24 mm (interquartile range [IQR] 24–26 mm) for all isolates and 18 mm (IQR 15–21 mm) for NDM producers. We observed significant variability between cefiderocol susceptibilities using EUCAST and CLSI breakpoints, such that 26% and 2% of all isolates, and 81% and 12% of the NDM producers were resistant to cefiderocol using EUCAST and CLSI interpretive criteria, respectively. Conclusions: Cefiderocol resistance rates among NDM producers are high using EUCAST criteria. Breakpoint variability may have significant implications on patient outcomes. Until more clinical outcome data are available, we suggest using EUCAST interpretive criteria for cefiderocol susceptibility testing.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; Mikrobiyoloji; BULAŞICI HASTALIKLAR; MİKROBİYOLOJİ; Life Sciences (LIFE); IMMUNOLOGY; MICROBIOLOGY; INFECTIOUS DISEASES; Genel İmmünoloji ve Mikrobiyoloji; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; General Immunology and Microbiology; Microbiology (medical); Infectious Diseases; bloodstream; Cefiderocol; CLSI; EUCAST; Klebsiella; NDM